PERDEBATAN HUKUM TERHADAP VAPE DI MATA DUNIA - Alfarizhi, Muhammad (Gapenas Publisher, 2023)
The development of the times has led to debates in the eyes of the world and in Indonesia itself it is still very common. So that this debate can affect these developments in the use of tobacco-type materials in society, namely conventional cigarettes and electric cigarettes. Cigarettes have been growing over time. Cigarettes can be divided into two types: there are conventional cigarettes, namely cigarettes which consist of cigarette wrapping paper rolled together with tobacco and enjoyed by burning them and electric cigarettes or vapes, namely cigarettes which consist of a machine that functions to heat liquid so that it becomes vapor containing various different flavors. exist in the liquid, in Indonesia some of these e-cigarettes are still imported from abroad compared to domestically. The current regulation underlying e-cigarettes and liquid liquids is contained in the Minister of Trade Regulation No. 86 of 2017 concerning Provisions for the Import of E-Cigarettes. Based on the facts in the field of e-cigarettes in circulation, they must first obtain a distribution permit from the competent authority in that country. So far, it turns out that the distribution of e-cigarettes is illegal because they do not yet have a license for vape distribution, because the distribution is not supervised and controlled. If liquid liquid containing liquid cannabis is found, for the benefit of consumers for security, safety and comfort in its use, it is necessary to immediately issue a distribution permit from the authorized institution so that before it reaches consumers or users of e-cigarettes and the liquid is guaranteed to be safe. This research itself was made to find out how the rules regarding permits for the distribution of vape/electric cigarettes and e-liquid e-cigarettes in positive law in Indonesia and consumer rights for guarantees in the distribution of e-cigarettes and liquid in positive law in Indonesia and their safety